Natural history of the anterior visual pathway after surgical decompression in patients with pituitary tumors. (3rd June 2015) - Won Hyung, RA; Chan, W; Starreveld, Y; Costello, F
Abstract : Introduction: Visual dysfunction is one of the primary indications for surgical management of pituitary tumors with the goal of terminating the progressive decline in vision. Unfortunately, it is difficult to predict how successful surgical decompression will be in these patients. The purpose of this study was to assess the structural changes seen in the anterior visual pathway after pituitary tumor resection. Methods: 13 patients (7F) underwent endoscopic tumor resection for pituitary macroadenoma. Each patient underwent a full ophthalmologic assessment including optical coherence tomography (OCT) preoperatively and postoperatively at 3-6months and 9-12months. Post-surgical changes in the retinal nerve fiber layer thickness (RNFLT) for each eye (N=26) were compared in cases with normal preoperative RNFLT (greater than 80 μm) versus those with abnormally thinned RNFLT (less than 80 μm). Results: For 9 cases with thinned RNFLT preoperatively (mean=70.1 μm±8.5), there was a significant decline in RNFLT at 3-6 months follow-up (mean change= −3.8 μm;p=0.002), which did not recover even at 9-12months after surgery (mean=67.6 μm±12.7). Contrastingly, eyes with normal RNFLT preoperatively (mean=89.7 μm±9.4) did not show significant postoperative thinning (mean change= −1.9 μm). Conclusion: Even after a complete surgical decompression, there are ongoing structural changes in the anterior visual pathway in patients with compressive neuropathy. There may be a point of no return where surgical decompression may not prevent further structural degeneration.